Numerical modeling of cracking behaviors for the rock-inclusion composite under dynamic tensile loading. (May 2023) - Wang, Lu; Zhu, Yujie; Mei, Cheng
Abstract: Rock-inclusion composites have been widely used in underground engineering, however, the impact of inclusions with varying physico-mechanical properties, such as the strength ratio and size, on cracking behaviors under dynamic tensile loading is still unclear. In this study, using a discrete element method (DEM), a series of numerical simulations are performed on the flattened Brazilian disc (FBD) specimens to simulate the split Hopkinson pressure bar (SHPB) tests. The numerical results indicate that both the inclusion size and strength ratio can influence dynamic responses of a rock-inclusion composite. In specimens with weak inclusions, the nominal tensile strength (NTS) value is proportional with the strength ratio but negatively correlated with the inclusion size. Strength ratios are primarily responsible for determining three failure modes in specimens. During the loading process, the characteristics of acoustic emission (AE) events generated from the microcracks in specimens are analyzed in terms of moment magnitude, failure mechanism, b -value, and frequency-magnitude distribution. Additionally, energy partitions evolve synchronously with cracking behaviors in specimens, and all the loading systems show a similar trend of energy conversion. This study may provide a promising DEM model for exploring dynamic tensile failures in rock-inclusion composites and explaining the complicated cracking behaviors in underground engineering.